Blood loss from transverse versus longitudinal uterine incision in abdominal myomectomy: a randomized controlled trial - Alaa Elguindy; Hosam Hemeda; Mohamed Esmat Shawky; Mohamed Elsenity; Medhat Adel Elsayed; Ahmed Fahim; Khaled Afifi; Maii Nawara (BMC, 2020)
Abstract Background It is unclear whether transverse uterine incision is non-inferior to longitudinal incision during myomectomy with regard to bleeding. Our aim was to compare between transverse and longitudinal uterine incisions in myomectomy. Methods A parallel randomized controlled single-blinded study in a university affiliated hospital, in the period between January 2017 and April 2018, in which 52 women candidates for abdominal myomectomy were randomized into transverse uterine incision or longitudinal uterine incision groups (26 in each group). Intraoperative blood loss (estimated directly by blood volume in suction bottle and linen towels and indirectly by difference between preoperative and postoperative hematocrit), operative time and postoperative fever were analyzed. Results No statistically significant difference was found between transverse and longitudinal incisions regarding intraoperative blood loss (389.7 ± 98.56 ml vs 485.04 ± 230.6 ml respectively, p value = 0.07), operative time (59.96 ± 16.78 min vs 66.58 ± 17.33 min respectively, p value = 0.18), and postoperative fever (4% vs 8.33%, p value = 0.6). Conclusion Transverse uterine incision does not cause more blood loss than longitudinal incision and is a reasonable option during abdominal myomectomy. Trial registration: NCT03009812 at clinicaltrials.gov, registered January 2017